Gas diffusion layer, preparation method thereof and fuel cell

By introducing graphene material into the gas diffusion layer of the fuel cell, reducing surface cracks of the microporous layer, improving hydrophobicity and gas transmittance, the problem of mass transfer loss in the fuel cell is solved, and the effects of high output power and high power density are achieved.

CN119674114APending Publication Date: 2025-03-21BEIJING GRAPHENE INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311229379.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

There is a problem of mass transfer loss in fuel cells, which leads to constraints on voltage drop and energy density, especially under high relative humidity and low relative humidity conditions.

Method used

A gas diffusion layer is designed, including a microporous layer and a substrate layer. The microporous layer consists of conductive material and graphene material. The addition of graphene material can reduce the number of cracks on the surface of the microporous layer and improve hydrophobicity and gas transmittance.

Benefits of technology

It effectively reduces mass transfer loss, improves the output power and power density of fuel cells, and maintains efficient performance under different relative humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674114A_ABST
    Figure CN119674114A_ABST
Patent Text Reader

Abstract

The invention discloses a gas diffusion layer, a preparation method thereof and a fuel cell. By simultaneously adding the graphene material and the carbon black into the preparation slurry of the microporous layer and reasonably controlling the proportion of the graphene material and the carbon black, the number of cracks on the surface of the microporous layer can be effectively reduced, the number of the cracks can be reduced by 2 / 3 compared with that of the microporous layer prepared by independently using the carbon black, and the contact resistance is reduced by 3% compared with that of the microporous layer prepared by independently using the carbon black; the output power of the fuel cell can be effectively improved. The preparation method disclosed by the invention is simple to operate, high in repeatability, controllable in quality and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a gas diffusion layer and a preparation method thereof, and a fuel cell. Background Art

[0002] Proton exchange membrane fuel cells are a way of converting chemical energy into electrical energy directly without carbon emissions, and are expected to exceed 60% energy conversion efficiency. Due to its low temperature working environment, long-term stability, fast charging, and high energy density, it is considered to be the next generation of energy conversion.

[0003] However, the existence of three types of losses in fuel cells that may cause voltage drop, namely polarization loss, ohmic loss and mass transfer loss, restricts the realization of its ultra-high energy density. If the gas cannot reach the catalyst in time, the chemical reaction rate of the electrode will be slow. If the water cannot be discharged in time, it will cause flooding of the catalyst layer or gas diffusion layer; if the water content is low, it will cause the proton exchange membrane to dehydrate, resulting in greater ohmic loss. In fuel cells, the voltage consumed by mass transfer loss can account for more than 70% of the total voltage drop, especially under high current density conditions. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a gas diffusion layer with a reasonable structure, which can reduce mass transfer loss, improve output power and has a high power density under low relative humidity and high relative humidity conditions. The gas diffusion layer comprises a microporous layer and a substrate layer, wherein the raw materials for preparing the microporous layer comprise: a conductive material and a graphene material; the mass percentage of the graphene material / (conductive material+graphene material) is 0.5% to 100%, wherein 1% to 2% is preferred.

[0005] According to a specific embodiment of the present invention, the median pore diameter of the microporous layer is between 20-40 nm, and the contact angle between the microporous layer and water is between 110° and 140°.

[0006] According to a specific embodiment of the present invention, the thickness of the microporous layer is 10-100 μm.

[0007] According to a specific embodiment of the present invention, the graphene material is selected from one or more of CVD-grown graphene, supercritical fluid-exfoliated graphene, and microwave-assisted reduced graphene oxide.

[0008] According to a specific embodiment of the present invention, the conductive material is carbon black; preferably, the carbon black is selected from acetylene black and carbon black Vulcan XC-72.

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned microporous layer, which specifically comprises the following steps:

[0010] (1) preparing a microporous layer slurry, wherein the slurry comprises a conductive material, a binder, a graphene material and a solvent;

[0011] (2) The slurry is coated on the surface of a substrate and fired.

[0012] According to a specific embodiment of the present invention, in step (1), the solvent is water and isopropanol, wherein the mass ratio of water to isopropanol is 1:50-50:1.

[0013] According to a specific embodiment of the present invention, in step (2), the calcination temperature is 60-350° C., and the calcination time is 10-60 min.

[0014] According to a specific embodiment of the present invention, the binder includes one or two of polyethylene glycol and polypropylene glycol, wherein the average molecular weight of the polyethylene glycol is 1000-5000 g / mol, such as 1000 g / mol, 2000 g / mol, 3000 g / mol, 4000 g / mol, and 5000 g / mol.

[0015] According to a specific embodiment of the present invention, the slurry further includes a hydrophobic treatment agent, which is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, polydimethylsiloxane, perfluoroethylene propylene copolymer, and perfluoropolyether; preferably, the hydrophobic treatment agent is polytetrafluoroethylene.

[0016] According to a specific embodiment of the present invention, based on 100% of the mass of the slurry, the content of the binder is 5%-50%; preferably, the content of the binder is 5%-20%.

[0017] Based on 100% of the mass of the slurry, the content of the hydrophobic treatment agent is 5%-50%; preferably, the content of the hydrophobic agent is 20%-30%.

[0018] A third object of the present invention is to provide a fuel cell comprising the above-mentioned gas diffusion layer or the gas diffusion layer prepared by the above-mentioned preparation method.

[0019] Beneficial effects:

[0020] The present invention can effectively reduce the number of cracks on the surface of the microporous layer by adding graphene material and carbon black to the slurry for preparing the microporous layer and reasonably controlling the ratio thereof. The number of cracks can be reduced by 2 / 3 compared with the number of cracks in the microporous layer prepared by using carbon black alone, and the contact resistance is reduced by 3% compared with the microporous layer prepared by using carbon black alone, which can effectively improve the output power of the fuel cell. When used to connect the catalyst layer and the gas diffusion layer, the contact resistance can be reduced, effective drainage can be achieved, the gas transmission efficiency can be improved, and the gas permeation and drainage functions can be balanced, thereby achieving a high efficiency of up to 1.12W / cm 2The output power of the nanostructured carbon nanotubes can reach 100W, and the power density is high under different relative humidity conditions. The preparation method of the invention is simple to operate, highly repeatable, quality controllable and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A graph showing the pore size distribution of the gas diffusion layer of the embodiment and the comparative example;

[0022] Figure 2 The gas permeability and water contact angle test results of the embodiments and comparative examples are shown;

[0023] Figure 3 a is a scanning electron microscope photograph of the microporous layer prepared in Comparative Example 2;

[0024] Figure 3 b is a scanning electron microscope photograph of the microporous layer prepared in Example 1;

[0025] Figure 3 c is a scanning electron microscope photograph of the microporous layer prepared in Example 2;

[0026] Figure 4 The polarization curves of the gas diffusion layers prepared in Example 1 and Comparative Example 2 at different cathode dew point temperatures are shown;

[0027] Figure 5 It shows the maximum output power of the fuel cell assembled with the gas diffusion layers of Examples 1-6 and Comparative Example 2 at different cathode dew point temperatures. DETAILED DESCRIPTION

[0028] The following further exemplifies the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0029] Example 1

[0030] A slurry was prepared by mixing 3.48 g of carbon black (Vulcan XC-72, average particle size of about 40 nm), 2.5 g of 60 wt% PTFE aqueous emulsion, 0.04 g of graphene material obtained by supercritical fluid exfoliation, 1.0 mL of isopropanol, 40.0 mL of deionized water, and 1.0 g of polyethylene glycol (average molecular weight = 4000 g / mol). The slurry was stirred by a mechanical stirrer (1000 r·min -1) was mixed for 1 hour and ultrasonicated for 1 hour. The mixing and ultrasonication process was repeated twice to obtain a slurry.

[0031] By coating the slurry on the substrate layer (TGP-H-060, ) on one side, with a thickness of 40 μm. The sample was placed in an oven and baked at 60° C. for 20 min, and then continued to be baked at 350° C. for 1 hour to obtain a microporous layer MPL-1.

[0032] Example 2

[0033] Except for the different amounts of graphene material and carbon black added by supercritical fluid exfoliation, other conditions are the same as those in Example 1. The specific contents are shown in Table 1.

[0034] Example 3

[0035] A slurry was prepared by mixing 3.48 g carbon black (Vulcan XC-72, average particle size of about 40 nm), 2.5 g 60 wt% PTFE aqueous emulsion, 0.04 g microwave-assisted grown graphene, 1.0 mL isopropanol, 40.0 mL deionized water, and 1.0 g polyethylene glycol (average molecular weight = 4000 g / mol). The slurry was stirred by a mechanical stirrer (1000 r / min) for 1 h. -1 ) was mixed for 1 hour and ultrasonicated for 1 hour. The mixing and ultrasonication process was repeated twice to obtain a slurry.

[0036] By coating the slurry on the substrate layer (TGP-H-060, ) on one side, with a thickness of 40 μm. The sample was placed in an oven and baked at 60° C. for 20 min, and then continued to be baked at 350° C. for 1 hour to obtain a microporous layer MPL-3.

[0037] Embodiment 4-6

[0038] Except for the different amounts of microwave-assisted grown graphene and carbon black added, other conditions are the same as those in Example 3. The specific contents are shown in Table 1.

[0039] Comparative Example 1

[0040] Provide commercial gas diffusion layer YLS-30T containing microporous layer.

[0041] Comparative Example 2

[0042] The graphene material was completely replaced with carbon black, and other conditions were the same as those in Example 1 to prepare a microporous layer.

[0043] The microporous layers prepared in Examples 1-4 and the gas diffusion layers prepared in Comparative Examples 1-2 were tested for pore size. The pore size test method was based on the national standard GB / T21650.1-2008 "Mercury intrusion and gas adsorption method for pore size distribution and porosity of solid materials, Part 1: Mercury intrusion method". The test results are shown in Table 1. Figure 1 shown.

[0044] Table 1 lists the amounts of graphene and carbon black used in preparing the microporous layers in Examples 1-6 and the corresponding microporous layers, as well as the pore sizes of the microporous layers in Examples 1-6 and Comparative Examples 1-2.

[0045] Table 1

[0046]

[0047] It can be seen from the data in Table 1 that the method of the present invention can obtain a microporous layer with a median pore size between 20-35 nm. The pore size of the microporous layer of the commercially available gas diffusion layer is much higher than the pore size of the microporous layer of the present invention.

[0048] The microporous layers of Examples 1-6 and Comparative Examples 1-2 were tested for gas permeability and water contact angle. The contact angle test method refers to the national standard GB / T30693-2014 "Measurement of the contact angle of plastic film with water". The air permeability test method refers to the national standard GB / T24218.15-2018 "Test methods for textile nonwovens, part 15: determination of air permeability". The test results are as follows: Figure 2 Combining Table 1 and Figure 2 It can be seen from the data that the microporous layer of the present invention is hydrophobic, which is more conducive to drainage and achieves a balance between air permeability and drainage.

[0049] Figure 3 Scanning electron micrographs of the microporous layers prepared in Comparative Example 2 and Examples 1 and 2 are shown. Figures ac are scanning electron micrographs of the microporous layer Comparative Example 2, MPL-1, and MPL-2, respectively. It can be seen from the figure that the cracks on the surface of the MPL are significantly reduced after adding the graphene material, and the number of cracks is getting smaller and smaller as the amount of graphene material added increases, proving that the addition of graphene material can effectively reduce the number of cracks.

[0050] The gas diffusion layers prepared in Examples 1-6 and Comparative Example 2 were assembled into fuel cells. The samples were assembled into a single 5×5 cm 2 Fuel cell. The membrane electrode assembly is made of a sandwich structure with a 15μm Proton exchange membrane coating added 0.25 / 0.50mgcm on the anode / cathode side -2Platinum, the prepared microporous layer coated with MPL is placed on both sides. A commercial sample (YLS-30T, comparative example 1) is used as a comparison, that is, a fuel cell is assembled in the same manner except that the gas diffusion layer prepared in the embodiment is not used. The assembled fuel cell is subjected to performance testing. Before the performance test, the membrane electrode assembly is activated by a 0.5V constant voltage for 1 hour. The inlet pressures of the anode and cathode are 1 and 0.4 bar, respectively. The anode gas supply rate is 0.42slpm, while the cathode is 1.74slpm. The operating temperature of the fuel cell is 70°C (temperature deviation is ±1°C, especially at high current density), and the dew point of the anode is set to 80°C (100% relative humidity). The relative humidity on the cathode side varies due to different dew points, 80°C (100%), 68°C (60%), and 45°C (20%). The lower limit voltage of the battery is set to 0.4V. During each chemical equilibrium period during the test, air is blown into the battery at a rate of 6slpm to remove excess water for 20 seconds. The dew point meter is placed at the outlet of the cathode side to measure the relative humidity, which is used to compare the water intake rate and water production rate. Figure 4 and Figure 5 shown.

[0051] Figure 4 These are polarization curves of the microporous layer MPL-1 prepared in Example 1 and the microporous layer MPL-7 prepared in Comparative Example 2 at different cathode dew point temperatures. Figure 5 is the maximum output power of the fuel cell at different cathode dew point temperatures. Figure 4 and 5 It can be seen that the microporous layer prepared by the method of the present invention has a higher output power under high relative humidity, and especially MPL-1 and MPL-4 have better performance. Because under this condition, the MPL surface has fewer cracks and the pore size is larger than MPL-7, which can achieve effective gas transport and liquid water discharge. Therefore, the microporous layer prepared under such conditions can be selected to assemble fuel cells.

[0052] Embodiments 1 and 4 of the present invention achieve a high power consumption of 1.12 W cm -2 The current density of the samples assembled from commercial microporous layers is 3-4 times higher than that of the samples assembled from commercial microporous layers. Of particular note is MPL-4, which uses 0.08g of microwave-assisted graphene, which has a current density higher than 1.2Wcm under different relative humidity conditions (i.e. 20%, 60%, and 100%). -2 The output power has the potential for multi-scenario applications.

[0053] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.

[0054] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.

Claims

1. A gas diffusion layer, characterized in that: The gas diffusion layer includes a microporous layer and a substrate layer, wherein the microporous layer is arranged on the surface of the substrate layer; wherein the raw materials for preparing the microporous layer include: a conductive material and a graphene material; the conductive material includes one or more of carbon black and graphite; the mass percentage of graphene material / (conductive material+graphene material) is 0.5% to 100%, wherein 1% to 2% is preferred.

2. The gas diffusion layer according to claim 1, characterized in that The median pore size of the microporous layer is between 20-40 nm, and the contact angle between the microporous layer and water is between 110° and 140°.

3. The gas diffusion layer according to claim 1, characterized in that: The graphene material is selected from one or more of CVD-grown graphene, supercritical fluid-exfoliated graphene, and microwave-assisted reduced graphene oxide.

4. The gas diffusion layer according to claim 1, characterized in that: The conductive material is carbon black; preferably, the carbon black is selected from acetylene black and carbon black Vulcan XC-72.

5. The method for preparing a gas diffusion layer according to any one of claims 1 to 4, characterized in that: The specific steps include: (1) preparing a microporous layer slurry, wherein the slurry comprises a conductive material, a binder, a graphene material and a solvent; (2) coating the slurry on the surface of a substrate and firing it.

6. The preparation method according to claim 5, characterized in that: In step (1), the solvent is water and isopropanol, wherein the mass ratio of the water to the isopropanol is 1:50-50:

1.

7. The preparation method according to claim 5, characterized in that: In step (2), the calcination temperature is 60-350° C. and the calcination time is 10-60 min.

8. The preparation method according to claim 5, characterized in that: The binder includes one or both of polyethylene glycol and polypropylene glycol, wherein the average molecular weight of the polyethylene glycol is 1000-5000 g / mol, such as 1000 g / mol, 2000 g / mol, 3000 g / mol, 4000 g / mol, and 5000 g / mol.

9. The preparation method according to claim 8, characterized in that: The slurry further comprises a hydrophobic treatment agent, which is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, polydimethylsiloxane, perfluoroethylene propylene copolymer, and perfluoropolyether; preferably, the hydrophobic treatment agent is polytetrafluoroethylene.

10. The preparation method according to claim 9, characterized in that: Based on 100% of the mass of the slurry, the content of the binder is 5%-50%; preferably, the content of the binder is 5%-20%.

11. A fuel cell, comprising the gas diffusion layer according to any one of claims 1 to 4 or the gas diffusion layer prepared by the preparation method according to any one of claims 5 to 10.